Genre-based analysis of English and Persian Research Article Abstracts in Mining Engineering Journals - Farzannia, Sara; Farnia, Maryam (Beyond Words, 2017)
The current research aimed to explore the rhetorical moves in abstracts of English and Persian Mining Engineering research articles. For this purpose, 60 abstracts written by native speakers of English and Persian were analyzed based on Hyland’s (2000) model of five rhetorical moves to explore the pattern of moves in abstract sections. Findings suggested that there were four conventional moves in abstracts in the English corpus (PMPrC), while there were five conventional moves in abstracts in the Persian corpus (IPMPrC). Results of statistical analyses show that there was a statistically significant difference in Purpose move in the two dataset. However, there were not any significance differences in the use of other moves such as product, method, and conclusion moves in the corpora. Keyword: Abstract, Genre, Move pattern, Mining Engineering